Game, Set, and Match - Kas Oosterhuis (Oz, 2001)
L’architecture est un jeu magnifique “Architecture is the masterly, correct and magnificent play of masses brought together in light” as Le Corbusier put it in his manifesto Towards A New Architecture. Everything has changed since, and we are ready for the new paradigm: “Architecture is the programmable hyperbody played skillfully by its masters with the speed of light.”